MOMENTUM INVESTING STRATEGY IN IDX: AN EXPERIMENT - Ronald W. Liem (Journal of Applied Finance & Accounting, 2012)
This research aims to test whether the Momentum investing strategy is better than passive investing strategy. The research method used is experiment design. The population observed is Kompas100 shares. The sample is filtered using several iterations based on the market performance as the momentum points and other fundamental factors to form optimal portfolios. The data used is the quarterly data. The t-test and Mann-Whitney means difference tests are performed to assess the differences of the results of momentum strategy and the market. The results show that momentum strategy provides higher returns than the market does.This experiment suggests that momentum investing strategy is applicable in IDX.